Fine Art Fellows : 1989-90. (Cheltenham : Cheltenham & Gloucester College of Higher Education (CGCHE), 1990)
Cunningham, Jeremy ; Lowe, Anthony ; Mulhall, Sarah ; Coda, Aine Nic Giolla ; Noble, Simon ; Ruark, Jacqueline
Fine Art Fellows : 1989-90, Department of Visual and Performing Arts, Cheltenham, 1990
boek